2021
DOI: 10.1177/2470547021991556
|View full text |Cite
|
Sign up to set email alerts
|

Equine-Assisted Activities and Therapies for Veterans With Posttraumatic Stress Disorder: Current State, Challenges and Future Directions

Abstract: Posttraumatic stress disorder is common among military Veterans. While effective treatments exist, many Veterans either do not engage in treatment or fail to achieve full remission. Thus, there is a need to develop adjunctive complementary interventions to enhance treatment engagement and/or response. Equine-assisted activities and therapies (EAAT) are one category of animal assisted interventions that might serve this function. The aim of this article is to review the current state and challenges regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 81 publications
0
7
0
2
Order By: Relevance
“…Equine based activities, particularly riding, are associated with well documented injury risks, as equines are large, powerful, sentient, prey- animals with herd instincts whose behaviour is not always predictable [ 52 ] and may lead to injury. Three of the review studies identified equine-related risks and provided detail about mitigation strategies utilized in their programs [ 26 , 27 , 29 ] while the remaining three mentioned ‘safety measures’ without providing detail.…”
Section: Discussionmentioning
confidence: 99%
“…Equine based activities, particularly riding, are associated with well documented injury risks, as equines are large, powerful, sentient, prey- animals with herd instincts whose behaviour is not always predictable [ 52 ] and may lead to injury. Three of the review studies identified equine-related risks and provided detail about mitigation strategies utilized in their programs [ 26 , 27 , 29 ] while the remaining three mentioned ‘safety measures’ without providing detail.…”
Section: Discussionmentioning
confidence: 99%
“…When referencing human services incorporating equines, in both popular media and academic literature, there exist widespread usage of unclear and imprecise terms [ 6 ]. This lack of standardization impedes replicable research and creates an environment where EAS interventions cannot be properly evaluated and scientifically developed [ 37 ]. Future researchers should work to standardize and optimize terminology surrounding human services incorporating equines.…”
Section: Discussionmentioning
confidence: 99%
“…Woods et al [6] provided a starting point to this end, but acknowledge that their recommendations were developed from consensus rather than unanimous decision making and identify their article as a living document. Prior to the resolution of terminology concerns, researchers should provide detailed Diaz et al Substance Abuse Treatment, Prevention, and Policy (2022) 17:81 protocol descriptions such that replicability is possible independent of naming convention [37].…”
Section: Standardized Terminology For Equine Interventionsmentioning
confidence: 99%
“…Recent work has attempted to assess the impact of EAI on individuals' stress with promising preliminary results. These studies have assessed participant stress through observational questionnaires and objective biological variables such as cortisol [11,[43][44][45] and Heart Rate Variation (HRV) [15]. Moreover, we have not found studies on the EAIs' impact on stress levels in subjects with 22q11.2 DS diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Equine-assisted interventions (EAI) have focused on three areas: equine-assisted therapies, equine-assisted education and learning, and adapted horseback riding [3]. EAIs are showing promising results in physical and psychological conditions [4], benefits being evidenced in pathologies' core symptoms as well as in symptomatology related to adaptation difficulties [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%